2021
DOI: 10.1101/2021.05.12.443782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic profiling of tissue environments critical for post-embryonic patterning and morphogenesis of zebrafish skin

Abstract: Regulation of neural crest derived pigment cells and dermal cells that form skin appendages is broadly similar across vertebrate taxa. In zebrafish, organized pigment stripes and an array of calcified scales form simultaneously in the skin during post-embryonic development. Understanding mechanisms that regulate stripe patterning and dermal morphogenesis may lead to discovery of fundamental mechanisms that govern development of animal form. To learn about cell types and potential signaling interactions that go… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 173 publications
(336 reference statements)
1
2
0
Order By: Relevance
“…However, we found that the xanthoblasts/xanthophore pattern of embryonic zebrafish was not affected in iridophore mutants. Adult csf1b mutants have recently been noted to exhibit a reduction in dorsal xanthophores (62), a phenotype akin to what we observed in embryonic csf1b mutants. It is possible that Csf1b executes similar function in both stages.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, we found that the xanthoblasts/xanthophore pattern of embryonic zebrafish was not affected in iridophore mutants. Adult csf1b mutants have recently been noted to exhibit a reduction in dorsal xanthophores (62), a phenotype akin to what we observed in embryonic csf1b mutants. It is possible that Csf1b executes similar function in both stages.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies reported Csf1a and Csf1b expression in iridophores of juvenile and adult zebrafish ( 30 ). Csf1b was also identified in hypodermis of juvenile/adult zebrafish ( 62 ). Different from the juvenile and adult stage, we found that embryonic Csf1a and Csf1b were differentially expressed in col1a2 + fibroblast and muscle progenitors instead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the excess of THs are being studied in transgenic and/or pharmacologically treated with THs animals (Shkil et al, 2012, Keer et al, 2019, Keer et al, 2022, Aman et al, 2023, Deal and Volkoff, 2020. Such studies have yielded a wealth of data of all sort of effects of THs on the development of cartilages, bones, scales and dentition in fish.…”
Section: Introductionmentioning
confidence: 99%
“…The TH deficiency is acquired via a transgene-mediated ablation of thyroid follicles and/or the pharmacological treatment of organism with the goitrogens - chemical agents suppressing synthesis of thyroid hormones or disrupting HPT axis. The effects of the excess of THs are being studied in transgenic and/or pharmacologically treated with THs animals (Shkil et al, 2012, Keer et al, 2019, Keer et al, 2022, Aman et al, 2023, Deal and Volkoff, 2020). Such studies have yielded a wealth of data of all sort of effects of THs on the development of cartilages, bones, scales and dentition in fish.…”
Section: Introductionmentioning
confidence: 99%